GENERAL CATALOGUE OF VARIABLE STARS: CURRENT STATUS AND NEW NAME-LISTS - Samus, N. N.; Kazarovets, E. V.; Kireeva, N. N.; Pastukhova, E. N.; Durlevich, O. V. (Одеські астрономічні публікації, 2010)
A short history of variable-star catalogs is presented. After the second World War, the International Astronomical Union asked astronomers of the Soviet Union to become responsible for variable-star catalogs. Currently, the catalog is kept electronically and is a joint project of the Institute of Astronomy (Russian Academy of Sciences) and Sternberg Astronomical Institute (Moscow University). We review recent trends in the field of variable-star catalogs, discuss problems and new prospects related to modern large-scale automatic photometric sky surveys, outline the subject of discussions on the future of the variable-star catalogs in the profile commissions of the IAU, and call for suggestions from the astronomical community.